Children's play profiles: contributions from child's temperament and father's parenting styles in a Portuguese sample - Santos, C.; Monteiro, L.; Ribeiro, O.; Vaughn, B. E. (Frontiers in Psychology, 2020)
Using a sample of Portuguese pre-school age children, we aimed to identify different play profiles based on teachers' descriptions of social and non-social behaviors; as well as characterize them in terms of children's characteristics (sex and temperament), and fathers' parenting styles (e.g. warmth and involvement or punitive strategies). The 243 children were distributed across four profiles (identified through a two-stage cluster analysis): Solitary/Reticent, Social Rough, Social, and Social Solitary. A univariate effect was found between play profiles and children's Effortful Control, as well as father's Punitive Strategies. In addition, a significant multivariate interaction was found between child's sex and the Solitary/Reticent and Social Rough profiles for father's Punitive Strategies. In this sample children in social play profiles seem to use diverse types of behaviors during their interactions with peers and being adjusted within the group. As children's early experiences with peers are a central context for a healthy development, a better understating of the diversity of play profiles, and its predictors is important for early interventions.